Pharmacological blockade of the mast cell MRGPRX2 receptor supports investigation of its relevance in skin disorders - Macphee, Colin H.; Dong, Xinzhong; Peng, Qi; Paone, Daniel V.; Skov, Per Stahl; Baumann, Katrine; Roethke, Theresa; Goldspink, Deborah A.; Pearson, Samuel K.; Wu, Zining (Frontiers in Immunology, 2024)
Introduction: Since MRGPRX2 is now recognized as the mast cell receptor for basic secretagogues, there's currently tremendous interest in whether MRGRPX2 could play an important role in various pruritic dermatoses such as chronic spontaneous urticaria. We therefore sought to identify new potent and selective antagonists to pharmacologically characterize the biological role of MRGPRX2.Methods: Various relevant in vitro, ex vivo and in vivo model systems were used to investigate the role of MRGPRX2. This included the study of freshly isolated human skin mast cells and human basophils as well as an ex vivo human skin microdialysis preparation. The additivity of MRGPRX2 and FcR1 mediated degranulation was also investigated. Human MRGPRX2 knock-in mice were generated to interrogate pharmacokinetic/pharmacodynamic (PK/PD) relationships since both antagonists studied were shown to be human specific.Results: Two novel and structurally distinct MRGPRX2 antagonists were identified with one, compound B, being orally active and demonstrating high potency in blocking Substance Pmediated degranulation using freshly isolated human skin mast cells (IC50 = 0.42 nM). Compound B also potently blocked Substance Pstimulated histamine release from resident mast cells in a human skin explant setup as well as blocking itch in an established behavioral scratching model using MRGPRX2 knock-in mice. Unlike human mast cells, Substance P failed to elicit a functional response in human basophils.These data fully support the investigation of MRGPRX2 receptor antagonists in mast cell driven allergic skin disorders such as chronic spontaneous urticaria.